PENGARUH IMPLEMENTASI GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Kurniati, Rani; Arofah, Anastasia Anggarkusuma; Maharani, Destin Alfianika (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2025)
This research focuses on evaluating how green accounting and environmental performance influence the financial outcomes of manufacturing companies listed on the Indonesian stock exchange during the 2019-2021 period. Using quantitative methods, this study scrutinizes the direct and combined impacts of these practices on financial performance, which serves as a crucial indicator of a company’s profitability. The study sampled 18 manufacturing companies, chosen through purposive sampling based on five specific criteria. Findings from this investigation reveal that green accounting practices have a distinctly negative impact on financial performance, whereas environmental performance does not show a significant influence on financial metrics. However, when considered together, green accounting and environmental performance collectively contribute significantly to financial performance. This underscores the complex interplay between environmentally sustainable practices and financial results in the manufacturing sector